Coming out: the experience of LGBT+ people in STEM - Ben Barres; Beth Montague-Hellen; Jeremy Yoder (Genome Biology, 2017)
Abstract Continuing with our Q&A series discussing issues of diversity in STEM fields, Genome Biology spoke with three openly LGBT+ researchers on their experiences in biology.